Peningkatan Efisiensi Poli Tanin Sebagai Dye Pada Dye Sensitized Solar Cell Menggunakan Crosslinker Glutaraldehyde - Hanifah Putri Indah Subriadi; Hardeli Hardeli (REACTOR: Journal of Research on Chemistry and Engineering, 2023)
Dye Sensitized Solar Cell (DSSC) is the latest generation of solar cells with dyes as absorbers of photons from sunlight. At this time, the DSSC efficiency obtained is still relatively low so that research on DSSC is still being developed to produce DSSC with higher efficiency. One of the methods used to increase the efficiency of DSSC is polymerization of dyes. Polymerization of dyes aims to increase conjugated double bonds. The more conjugated double bonds, the more photons will be absorbed so that more electrons will flow. In this study, tannins were used as dyes. In the tannin polymerization process, crosslinking agents are used to bind tannin monomers with other tannin monomers. the variable in this study was the volume of the glutaraldehyde crosslinking agent (1.5 mL, 2.5 mL, 3 mL). The results of this study obtained the highest DSSC efficiency of 12.20% at a volume of 2.5 mL of crosslinking agent.